The Laser-Driven X-ray Big Area Backlighter (BABL): Design, Optimization, and Evolution. (May 2016) - Flippo, Kirk; DeVolder, Barbara; Doss, Forrest; Kline, John; Merritt, Elizabeth; Loomis, Eric; Capelli, Deanna; Schmidt, Derek; Schmitt, Mark J.
Abstract: The Big Area BackLigher (BABL) has been developed for large area laser-driven x-ray backlighting on the National Ignition Facility (NIF), which can be used for general High Energy Density (HED) experiments. The BABL has been optimized via hydrodynamic simulations to produce laser-to-x-ray conversion efficiencies of up to nearly 5%. Four BABL foil materials, Zn, Fe, V, and Cu, have been used for He-α x ray production.